PENGEMBANGAN MODUL PEMBELAJARAN STATISTIKA PENDIDIKAN BERBASIS MULTIMEDIA INTERAKTIF - Abdul Wahab; Junaedi; Rezkikah Muis; Nur Aeni F (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and validate an interactive multimedia module for the Educational Statistics course to improve students’ statistical literacy and learning outcomes in higher education. The background of the research lies in the low level of statistical literacy of students and the tendency for learning activities to be dominated by theoretical delivery without meaningful interaction or contextual exploration. The research follows a development model with stages of analysis, design, development, implementation, and evaluation, involving subject matter experts, instructional media specialists, and undergraduate students as research participants. Data were collected through expert validation sheets, practicality questionnaires, and pretest–posttest learning assessments. The results show that the developed module meets the criteria of being highly valid in terms of content accuracy, instructional design, multimedia display, and usability. The practicality test demonstrates positive responses from both lecturers and students, indicating that the module is easy to use, attractive, and supportive of autonomous learning. The effectiveness test also shows a significant increase in students’ statistical literacy, proven by a higher N-Gain score in the experimental class compared to the control class. These findings prove that the interactive multimedia module can enhance conceptual understanding, analytical skills, and critical thinking in statistical learning. The study recommends further refinement through gamification features and real dataset simulations to expand user experience and future implementation on different subjects and educational levels.